1980
DOI: 10.1111/j.1432-1033.1980.tb04731.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of mRNA from Bovine Pituitary. The Cell-Free Synthesis of the alpha and beta Subunits of Luteinizing Hormone

Abstract: RNA derived from bovine steer pituitary was translated in wheat germ cell-free extracts containing [35S]methionine. Antisera generated against purified denatured a and fi subunits of lutropin were used to demonstrate the synthesis of both proteins in vitro. The immunoprecipitated products of the cell-free system were resolved on sodium dodecyl sulfate/polyacrylamide gels and it was observed that the molecular weight of the immunoprecipitated a subunit protein was approximately 14000, while that of the p protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition, cell-free translation studies have shown that both pituitary a-subunit (17) and LH,3-subunit (21) mRNA activity levels are lower in gonadal-steroid hormonetreated OVX ewes than in untreated GDX controls (7). Using (16)(17)(18)(19). This hypothesis was based upon the repeated observation that serum and intracellular levels of pituitary and placental free a-subunit exceed the serum and intracellular levels of intact glycoprotein hormones (14,15,40,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, cell-free translation studies have shown that both pituitary a-subunit (17) and LH,3-subunit (21) mRNA activity levels are lower in gonadal-steroid hormonetreated OVX ewes than in untreated GDX controls (7). Using (16)(17)(18)(19). This hypothesis was based upon the repeated observation that serum and intracellular levels of pituitary and placental free a-subunit exceed the serum and intracellular levels of intact glycoprotein hormones (14,15,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The excess production of a-subunits over LHf-subunits (14,15) has suggested that the rate of LHfl-subunit synthesis determines the amount of intact LH produced (16)(17)(18)(19). Several studies at the pretranslational level using cell-free translational analyses have indicated that the levels of a-and LHfl-subunit messenger RNAs (mRNAs) are elevated in castrate animals (17)(18)(19)(20), and that they decrease with gonadal steroid replacement (7,9,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17000 was found. Asomewhat loweri21, (16000-18 000) than that determined by us for pre-rLqO has been determined by others for bovine pre-Lt1/3 [9,24].…”
Section: 53mentioning
confidence: 99%
“…An app. M, 14 000 has been reported for bovine pre-LHa [8,24] and for pre-TSHa synthesized by mRNA from mouse thyrotropic tumor [25,26]. However, comparing prea subunits synthesized in cell-free conditions by RNA from bovine pituitaries and from mouse pituitary tumor 1271, in both cases IV,.…”
Section: 53mentioning
confidence: 99%